2011
DOI: 10.1111/j.1468-3083.2011.04315.x
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal susceptibility patterns of yeasts and filamentous fungi isolated from nail infection

Abstract: C. parapsilosis was the most common fungal species isolated from patients with onychomycosis. The different response obtained by in vitro susceptibility testing to drugs shows the importance of these methods to assist clinicians in choosing the best therapeutic option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 40 publications
10
19
0
Order By: Relevance
“…One limitation of this study is that we did not measure the in vitro activity of other azoles against these isolates. However, the luliconazole MIC range, MIC 50 and MIC 90 values, and GM MICs that were measured in the current study compared favorably those reported in the literature for other azoles against dermatophytes, including itraconazole, voriconazole, posaconazole, ketoconazole, and the investigational agents efinaconazole and ravuconazole (Table 3) (15)(16)(17)(18)(19)(20). Although direct in vitro comparisons with newer azoles are warranted, none of these other azoles, except for itraconazole, currently have an FDA-approved indication for the treatment of onychomycosis.…”
supporting
confidence: 68%
“…One limitation of this study is that we did not measure the in vitro activity of other azoles against these isolates. However, the luliconazole MIC range, MIC 50 and MIC 90 values, and GM MICs that were measured in the current study compared favorably those reported in the literature for other azoles against dermatophytes, including itraconazole, voriconazole, posaconazole, ketoconazole, and the investigational agents efinaconazole and ravuconazole (Table 3) (15)(16)(17)(18)(19)(20). Although direct in vitro comparisons with newer azoles are warranted, none of these other azoles, except for itraconazole, currently have an FDA-approved indication for the treatment of onychomycosis.…”
supporting
confidence: 68%
“…Overall, the geometric mean MIC of itraconazole for half of the isolates was Ͻ0.1 mg/liter, and the highest GM was 0.59 mg/liter (16), followed by 0.42 mg/liter (8). Our results showed good in vitro activity of itraconazole against T. rubrum (GM, 0.26 mg/liter); however, itraconazole was less active than the three new triazoles tested.…”
mentioning
confidence: 54%
“…For many years, griseofulvin was the only approved systemic antidermatophytic agent (4). However, nowadays, many potent antifungal agents are available for the treatment of dermatophytosis, such as allylamines and triazoles, which have more potent activity and fewer side effects (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). The expansion of information on in vitro susceptibility testing of dermatophytes to new antifungal agents will help in the selection and development of antifungal drug regimens.…”
mentioning
confidence: 99%
“…Moreover, this species represents frequent cause of onychomycosis in several countries, including Brazil (4) , Chile (16) , México (17) , and Iran (18) . Although all 87 isolates of C. parapsilosis studied in our work have been identifi ed by phenotypic methods, we were not able to differentiate among the C. parapsilosis complex species, which are phenotypically identical.…”
Section: In Vitro Susceptibility Testingmentioning
confidence: 99%
“…Candida parapsilosis is a common yeast species found in cases of onychomycosis and candidemia associated with infected intravascular devices (3) (4) (5) (6) . In State of Goiás, Brazil, C. parapsilosis was found in 52.5% of nail samples and was the second most commonly isolated species (24.2%) from blood cultures (4) (7) . Previous work has shown that C. parapsilosis isolates may exhibit genotypic differences, allowing the classification of new species by restriction polymorphism analysis of the secondary alcohol dehydrogenase (SADH) gene.…”
mentioning
confidence: 99%